HUBUNGAN PENGETAHUAN DAN PENDIDIKAN IBU HAMIL TERHADAP ASI EKSLUSIF PADA IBU HAMIL - Siti Zulhijjah; Filza Yudrika (Ensiklopedia of Journal, 2026)
Background: The coverage of exclusive breastfeeding in Indonesia has not yet reached the national target of 80%. A mother's readiness to provide breast milk is heavily influenced by internal factors, particularly the level of education and knowledge acquired during pregnancy.Objective: This study aims to analyze the relationship between the level of education and knowledge of third-trimester pregnant women regarding readiness for exclusive breastfeeding.Methods: This research is a quantitative analytical study with a cross-sectional design. The study was conducted on 30 pregnant women selected using total sampling. Data were collected using structured questionnaires and analyzed using the Chi-Square statistical test at a 95% confidence level (α =0.05). Results: Univariate analysis showed that the majority of respondents had secondary education (40%) and good knowledge (46.7%). Bivariate analysis indicated a significant relationship between education level and exclusive breastfeeding readiness (p=0.012) and a highly significant relationship between knowledge level and exclusive breastfeeding readiness (p=0.001). Conclusion: There is a significant relationship between the education and knowledge levels of pregnant women and their readiness for exclusive breastfeeding. Health workers are advised to increase the intensity of lactation education in prenatal classes, especially for groups with lower educational backgrounds, to improve exclusive breastfeeding coverageKeywords: : Education, Knowledge, Pregnant Women, Exclusive Breastfeeding